Pengaruh Usia, Pendidikan, dan Pendapatan terhadap Literasi Keuangan PT Niaga Makmur Palembang - Jauhari, Muhamad Imam; Elizabeth, Sri Megawati (Universitas Multi Data Palembang, 2025)
This study aims to investigate the impact of Age, Education, and Income on Financial Literacy at PT. Niaga Makmur. Data was collected through a questionnaire completed by 50 employee respondents from PT. Niaga Makmur, as well as secondary data from relevant literature and journals. Data analysis employed reliability testing, validity testing, classical assumption testing, multiple regression analysis, and hypothesis testing. The results of this study indicate that Age, Education, and Income have a significant simultaneous impact on Financial Literacy.